Cultural heritage in in-service teacher training (Educational Knowledge, 2022)
This research analyzes cultural heritage and its implementation as a didactic tool in in-service teacher training. It addresses cultural heritage in the development of content by in-service teachers in a pedagogical manner. Furthermore, it proposes the implementation of training courses based on project-based methodology, focusing on specific aspects of Paraguayan culture. The activities carried out in the theoretical and practical modules correspond to in-service education professionals from different levels of the Paraguayan education system. The problem addressed by this research lies in the complete lack of cultural heritage training for in-service teachers, both as a core subject and as an elective, within the Paraguayan context. Two studies are presented: the first compares cultural heritage projects in selected countries in Europe and Latin America, as well as the absence of cultural heritage and models of heritage education. The second describes didactic tools for classroom application in different subjects within the curriculum. The methodology is carried out using a qualitative and interpretive approach. The results indicate significant differences between European and Latin American countries: on the one hand, innovation in the use of cultural heritage in Europe with in-service teacher training programs; on the other hand, ongoing professional development in institutions such as museums. These programs are tailored to the needs of in-service teachers. However, in the Latin American context, these programs are still under development for implementation in classrooms.
Keywords: Cultural heritage; educational model; cultural innovation; program content; professional training